Impact of social media usage on sport participation and well-being of English premier league fans - Lee, Kar Chun (2019)
Social media have arisen as a vital mechanism for socialization today. This study investigates the impact of increased social media usage on English Premier League fans and aims to examine the relationships between (1) social media usage and sport participation, (2) social media usage and well-being, (3) moderation effect of fan loyalty between social media usage and sport participation, and (4) moderation effect of fan loyalty between social media usage and well-being. This study utilized a survey questionnaire consisting of questions utilizing a 5-point Likert scale. The questions were adapted from the study by Kim, Liu and Shan (2017), Kim, Kim and Kim (2016) and Karjaluoto, Munnukka and Salmi (2016). 404 participants were recruited with the pre requisite of following the English Premier League. Pearson correlation and multiple regression analyses were carried out and it was found that (1) social media usage was related positively to sport participation, (2) social media usage was related positively to well-being, (3) fan loyalty did not moderate the relationship between social media usage and sport participation, and (4) fan loyalty moderated the relationship between social media usage and well-being. This study will broaden the understanding of the impacts of social media usage on English Premier League fans, and in turn provide valuable information for sport managers to utilize these social media platforms to increase the sport participation and well-being of these fans.